Synthesis and Characterization of RbxMn[Fe(CN)]6 and Mn3[Cr(CN)6]2 - Phu, Phung Kim; Thuan, Nguyen Minh; Trung, Tran Nam; Minh, Nguyen Van (Communications in Physics, 2011)
We present the synthesis and detailed characterization of RbxMn[Fe(CN)]6 and Mn3[Cr(CN)6]2 compounds. The composition of the materials significantly depends on the preparation conditions. Analysis of Raman spectroscopic results and X-ray powder diffraction data yielded a further assessment of the changes in structural features. The characteristic individual magnetic behavior, as well as the metal-to-metal charge-transfer capabilities of the various samples, could be related to significant changes within the structure that appear to be associated with the synthesis method used.